2010
DOI: 10.1073/pnas.1002431107
|View full text |Cite
|
Sign up to set email alerts
|

Double dissociation of two cognitive control networks in patients with focal brain lesions

Abstract: Neuroimaging studies of cognitive control have identified two distinct networks with dissociable resting state connectivity patterns. This study, in patients with heterogeneous damage to these networks, demonstrates network independence through a double dissociation of lesion location on two different measures of network integrity: functional correlations among network nodes and within-node graph theory network properties. The degree of network damage correlates with a decrease in functional connectivity withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
155
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 33 publications
13
155
4
Order By: Relevance
“…second, that lesions to locations with low scores on these measures will have more limited consequences. These predictions align with and advance an emerging perspective on the importance of connector regions in brain networks (1,2,14).…”
Section: Significancesupporting
confidence: 76%
“…second, that lesions to locations with low scores on these measures will have more limited consequences. These predictions align with and advance an emerging perspective on the importance of connector regions in brain networks (1,2,14).…”
Section: Significancesupporting
confidence: 76%
“…Thus, when the costs of adding connections is significant in the overall energy budget of an organism, as is likely for the brain, modular networks with weaker connectivity between modules than within the modules are superior to nonmodular networks, as they function as well and adapt faster without consuming as much energy. Moreover, a double dissociation was found between two modules, such that, for both modules, damage to a node in one module only caused dysfunction (i.e., a decrease in functional connectivity) in the damaged module, suggesting their autonomy (78). Finally, empirical functional connectivity studies have shown that modules are weakly functionally connected to each other, likely because their computations are predominantly distinct, suggesting modular function (6,7,16,36,79).…”
Section: Discussionmentioning
confidence: 96%
“…Alterations of functional connectivity in heterogeneous lesions have been previously explored by Nomura et al 11 Patients were examined using a single scan at least 5 months poststroke or injury. The results demonstrated double dissociation of two cognitive control networks (frontoparietal and cinguloopercular).…”
Section: Effects Of Lesions On Functional Network S Ovadia-caro Et Almentioning
confidence: 99%
“…As brain functions emerge from interacting regions that are part of a network topology, [1][2][3][4] so too can alterations across networks coincide with various pathological states such as disorders of consciousness, 5,6 Alzheimer's disease, 7 neuropsychiatric disorders, 8 and stroke. [9][10][11][12][13] Stroke lesions provide a unique model of how local damage can result in long-distance alterations. Similar structural damage has been shown to result in different levels of impairment to functionality, and patients can present multiple deficits in the acute phase that are not easily attributed to the direct effect of the focal lesion.…”
Section: Introductionmentioning
confidence: 99%